Morphological Phenotyping of Organotropic Brain- and Bone-Seeking Triple Negative Metastatic Breast Tumor Cells - DeCastro, Ariana Joy L.; Pranda, Marina A.; Gray, Kelsey M.; Merlo-Coyne, John; Girma, Nathaniel; Hurwitz, Madelyn; Zhang, Yuji; Stroka, Kimberly M. (Frontiers in Cell and Developmental Biology, 2022)
Triple negative breast cancer (TNBC) follows a non-random pattern of metastasis to the bone and brain tissue. Prior work has found that brain-seeking breast tumor cells display altered proteomic profiles, leading to alterations in pathways related to cell signaling, cell cycle, metabolism, and extracellular matrix remodeling. Given the unique microenvironmental characteristics of brain and bone tissue, we hypothesized that brain- or bone-seeking TNBC cells may have altered morphologic or migratory phenotypes from each other, or from the parental TNBC cells, as a function of the biochemical or mechanical microenvironment. In this study, we utilized TNBC cells (MDA-MB-231) that were conditioned to metastasize solely to brain (MDA-BR) or bone (MDA-BO) tissue. We quantified characteristics such as cell morphology, migration, and stiffness in response to cues that partially mimic their final metastatic niche. We have shown that MDA-BO cells have a distinct protrusive morphology not found in MDA-P or MDA-BR. Further, MDA-BO cells migrate over a larger area when on a collagen I (abundant in bone tissue) substrate when compared to fibronectin (abundant in brain tissue). However, migration in highly confined environments was similar across the cell types. Modest differences were found in the stiffness of MDA-BR and MDA-BO cells plated on collagen I vs. fibronectin-coated surfaces. Lastly, MDA-BO cells were found to have larger focal adhesion area and density in comparison with the other two cell types. These results initiate a quantitative profile of mechanobiological phenotypes in TNBC, with future impacts aiming to help predict metastatic propensities to organ-specific sites in a clinical setting.